Impact of super apps on the nutrition transition in low- and middle-income countries: Evidence from Indonesia - Elza Samantha Elmira; Asep Suryahadi (University of Bonn, Center for Development Research (ZEF), 2025)
Many low- and middle-income countries (LMICs) are experiencing a nutrition transition from traditional diets to high-energy, processed foods, increasing non-communicable disease risks. Digitalization of food systems plays a significant role in shaping this transition. This paper investigates the impact of super app expansions (including food delivery, ridesharing, and other daily life assistance) on nutritional outcomes and the underlying mechanisms. Staggered district-level adoption of Indonesia's two largest digital platforms, Gojek and Grab from 2015 to 2018, is used. This information is combined with the health dataset from Indonesia's Basic Health Survey (Riskesdas) and food consumption data from the National Socioeconomic Survey (Susenas). To address the endogeneity issue associated with the correlation between super app entry decisions and nutritional outcomes, we use doubly robust difference-in-differences, which incorporates baseline covariates ensuring a conditional parallel trend. The results show that super apps contribute to an increase in BMI scores, particularly among individuals who are already overweight and obese. This effect is especially driven by the online food delivery feature and is more pronounced in cities than regencies and among individuals with employment, above median income, and education beyond primary school. These increases could be attributed to unhealthy food consumption (i.e., salty and prepared foods). Our findings suggest that super apps may exacerbate malnutrition. On the other hand, we find underweight reduction in the cities and an overall increase in fruit and meat consumption, indicating super apps' potential to improve malnutrition. These findings highlight the role of super apps in the nutrition transition in LMICs.
Keywords: I15; O14; R40; 330; digital platform; super app; online food delivery; nutrition transition; overweight; obesity